Projetos de vida e escolha profissional: dilemas dos estudantes do ensino médio - Costa, Elenara Farias Lazzarotto da (2016)
During adolescence, besides experiencing physical and emotional changes, the teenager begins to design his or her life. These projects include topics such as building a family, getting a good job and attaining financial stability. This thesis was divided in two studies. In both studies participated 243 students of both sexes, aged 13 to 19 years. The instruments used were a socioeconomic questionnaire and the Incomplete Sentences Game (ISG). Information obtained in ISG were subjected to content analysis. The first study presents the projects for the future students from public high schools have. On ISG, students were asked to complete the following sentences aiming to analyze and discuss future projects: "My future plans are," "After school, I wish," "I would not want to" and "When thinking about the future, I". In sentences "My plans for the future" and "After school, I wish," the categories with higher percentage were "studying" and "work." In the sentences "My plans for the future are" and "When thinking about the future, I" answers revealed that students aim to achieve financial independence and be successful. In the sentence "I would not want to" the categories with higher percentages were: "fail", "do what you do not like" and "stop the studies". "Thinking about the future" revealed three categories: "positive feelings", "be successful" and "negative feelings". The category "do not know" was little used, suggesting that students have their future projects defined. The second study, in turn, presents the views of students from public high schools about career choice and work. Students were instructed to complete the following sentences: "To choose a profession is," "Having a profession means", "My job has to", "In my work I intend to" and "In my work I do not want ". In the sentence "To choose a profession is" three categories showed higher percentage: "is to decide the future", "is to be sure" and "it is difficult". The sentence "To have a profession means" revealed the categories: "to be successful (also present in the sentences "To choose a profession is , Having a profession means , My job has to , and In my work I want ) and doing what you want (also present in the sentence My job has to"), with higher percentages. The category that stood out from the answers was being a good professional , present in the sentences "Having a profession means", "My job has to", "In my work I intend to" and "In my work I do not want with high percentage.